Choreo-athetosis and Encephalopathy Induced by Phenytoin. Issue 5912 (27th April 1974) - McLellan, D. L.; Swash, M.
Abstract : Two patients with intractable epilepsy who had been treated with various combinations of anticonvulsant drugs developed phenytoin encephalopathy. In both patients choreo-athetoid involuntary movements were prominent. Blood phenytoin concentrations were above 30 μg/ml. When phenytoin was given in smaller doses and its level in the blood fell the involuntary movements and other clinical manifestations disappeared.